Analysis of Stakeholders' Expectations for Dairy Sector Development Strategies from a Central-Eastern and Western European Perspective - Abele Kuipers; Agata Malak-Rawlikowska; Aldona Stalgiene; Marija Klopcic (German Journal of Agricultural Economics (GJAE), 2017)
The development paths chosen by farmers and the critical success factors involved can be better understood when the business context in which these farmers operate is known. Also, interaction in the chain contributes to the strength of the chain. This raises questions such as do chain parties cooperate and is there a certain consensus concerning the future strategic route? This article provides a unique analysis of how stakeholders envisage the future of dairy farming in a period of radical policy change and what barriers they foresee to their objectives. The questionnaire used examined perceptions on development strategies, availability of resources, opportunities & threats (O&T), farmer skills and future expectations. In 2015 and early 2016, a total of 161 completed questionnaires were collected from stakeholders (leading persons in the dairy chain) in the Netherlands, Slovenia, Lithuania and Poland. Data were analysed by PCA, ANOVA, cluster and stepwise regression methods. Eight strategic clusters of stakeholders were found. Farm expansion and specialisation was the most expected development strategy (57% of stakeholders). Almost one fourth of the stakeholders took a wait and see approach, of which 15% looked for opportunities to activate at a particular moment in time, while 8% were generally pessimistic about the future. Diversification in combination with organic farming was chosen by 5% of the stakeholders, 10% of stakeholders focused on cooperation, service and high tech, and another 5% placed their trust in skills, subsidies and labour. The opinions of stakeholders were highly affected by the country of origin, while only minor variations in opinions were observed between different categories of stakeholders. Polish stakeholders showed the most specialised view on the dairy chain, but they scored relatively low on cooperation. Development towards diversification and organic agriculture received higher scores in Slovenia and Lithuania compared to the Netherlands and especially to Poland. Netherlands' stakeholders were the most positive about the future e.g. they foresee expansion and market opportunities. It was shown that strategies, resources and O&T each directly affect future expectations, which was in agreement with the hypothetical model used.
Keywords: 330